(untitled) (Argos, 2025)
It is known that in Ancient India there were issues of religious origin that led the way to extraordinary scientific developments. In particular, there were important developments with regards to language. One of the consequences of such development is the Nirukta of Yāska, which is the most ancient corpus of etymological analysis known to this day. The purpose of the following article is to analyze the basic principles of the Nirukta of Yāska; its value and underlying ideology. The article also talks about all that the Nirukta of Yāska has given to other branches of the sciences of languages such as semantics, phonetics, dialectology, the philosophy of language, the history of linguistics, etc.